Realigning thunder and lightning: temporal adaptation to spatiotemporally distant events. - Jordi Navarra (Public Library of Science (PLoS), 2013)
The brain is able to realign asynchronous signals that approximately coincide in both space and time. Given that many experience-based links between visual and auditory stimuli are established in the absence of spatiotemporal proximity, we investigated whether or not temporal realignment arises in these conditions. Participants received a 3-min exposure to visual and auditory stimuli that were separated by 706 ms and appeared either from the same (Experiment 1) or from different spatial positions (Experiment 2). A simultaneity judgment task (SJ) was administered right afterwards. Temporal realignment between vision and audition was observed, in both Experiment 1 and 2, when comparing the participants' SJs after this exposure phase with those obtained after a baseline exposure to audiovisual synchrony. However, this effect was present only when the visual stimuli preceded the auditory stimuli during the exposure to asynchrony. A similar pattern of results (temporal realignment after exposure to visual-leading asynchrony but not after exposure to auditory-leading asynchrony) was obtained using temporal order judgments (TOJs) instead of SJs (Experiment 3). Taken together, these results suggest that temporal recalibration still occurs for visual and auditory stimuli that fall clearly outside the so-called temporal window for multisensory integration and appear from different spatial positions. This temporal realignment may be modulated by long-term experience with the kind of asynchrony (vision-leading) that we most frequently encounter in the outside world (e.g., while perceiving distant events).